Solidarity of Madura Immigrants in Overseas Desa Jemparing Kecamatan Longikis Paser District: Solidaritas Imigran Madura di Perantauan Desa Jemparing Kecamatan Longikis Kabupaten Paser - Jafar, Jafar; Hakim, Aji Qamara (Progress In Social Development, 2020)
ABSTRACT: The purpose of this study was to find out and describe in-depth the Solidarity of Madurese immigrants in Jemparing Village, Long Ikis District, Paser Regency. The research method used in this research is descriptive explorative research. In this research, the researcher wants to explore more deeply related to Madurese ethnic values ​​and norms, leadership systems, community stratification systems, community religious rituals, routine community activities that attach the community, conflict resolution mechanisms within the community and outside the community, mechanisms network building with Madurese ethnic communities in other areas and solidarity with Madurese immigrants in Jemparing Village using Emile Durkheim's theory of organic solidarity and mechanical solidarity. The results showed that the Solidarity of Madurese Immigrants in Perantau, Jemparing Village, Long Ikis District, Paser Regency, was going well, meaning that the solidarity that was built was quite solid. This is based on the patterns of interaction that are built between fellow Madurese ethnicities and with the surrounding community through several methods. Also, to be accepted in the local community, Madurese immigrants who are in Jemparing Village try to accept the customs/culture of the local community as a process of assimilation but do not forget their local customs/culture. Apart from that, organic solidarity and mechanical solidarity can go hand in hand in the daily life of Madurese immigrants who are in Jemparing Village, to be precise in the Ombe area. Tujuan dari penelitian ini adalah untuk mengetahui dan menggambarkan secara mendalam mengenai Solidaritas Imigran Madura di Perantauan Desa Jemparing Kecamatan Long Ikis Kabupaten Paser.Metode penelitian yang peneliti gunakan pada penelitian kali ini yaitu jenis penelitian deskriptif exsploratif. Pada penelitian kali ini peneliti ingin mengexsplor jauh lebih dalam terkait dengan nilai dan norma Etnis Madura, sistem kepemimpinan, system stratifikasi komunitas, ritual-ritual keagamaan komunitas, kegiatan-kegiatan rutin komunitas yang melekatkan komunitas, mekanisme penyelesaian konflik dalam komunitas dan luar komunitas, mekanisme pembangunan jaringan dengan komunitas Etnis Madura di wilayah lain dan solidaritas Imigran Madura di Desa Jemparing dengan menggunakan teori dari Emile Durkheim tentang solidaritas organik dan soldaritas mekanik. Hasil penelitian menunjukkan bahwa Solidaritas Imigran Madura di Perantauan Desa Jemparing Kecamatan Long Ikis Kabupaten Paser berjalan dengan baik, artinya bahwa solidaritas yang terbangun cukup solid. Hal itu berdasar pada pola interaksi yang dibangun baik antar sesama etnis Madura maupun dengan masyarakat sekitar melalui beberapa metode. Selain itu untuk dapat diterima dalam masyarakat setempat Imigran Madura yang berada di Desa Jemparing mencoba menerima adat-istiadat/budaya masyarakat setempat sebagai proses pembauran, tetapi tidak melupakan adat-istiadat/budaya local mereka. Selain itu solidaritas organik dan solidaritas mekanik dapat berjalan beriringan di dalam kehidupan sehari-hari Imigran Madura yang berada di Desa Jemparing, tepatnya di wilayah Ombe.